2012
DOI: 10.1177/0363546512442334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Acute Inflammatory Response of Two Commercial Platelet-Rich Plasma Systems in Healthy Rabbit Tendons

Abstract: Background: Numerous studies have shown platelet-rich plasma (PRP) preparations differ with respect to the inclusion of certain blood components, which may affect the host’s cellular response. Hypothesis: This study evaluated the inflammatory effect of Biomet GPS III leukocyte-rich PRP (LR-PRP) versus MTF Cascade leukocyte-poor PRP (LP-PRP) after intratendinous injection in an animal model. The authors anticipated that LR-PRP would incite a greater acute inflammatory response than LP-PRP. Study Design: Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
219
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(228 citation statements)
references
References 40 publications
1
219
0
7
Order By: Relevance
“…7,[9][10][11]14 Nonetheless, leukocyte-rich PRP may produce local inflammatory reactions. 10,11,[15][16][17] At one year, improvement in pain was greater after leukocyte-poor PRP injection than bupivacaine, corticosteroid, autologous blood, or leukocyte-rich PRP injection (Table 3). 7,[9][10][11]17 In our study, none of the patients who received leukocytepoor PRP complained of an increased post-injection pain.…”
Section: Discussionmentioning
confidence: 99%
“…7,[9][10][11]14 Nonetheless, leukocyte-rich PRP may produce local inflammatory reactions. 10,11,[15][16][17] At one year, improvement in pain was greater after leukocyte-poor PRP injection than bupivacaine, corticosteroid, autologous blood, or leukocyte-rich PRP injection (Table 3). 7,[9][10][11]17 In our study, none of the patients who received leukocytepoor PRP complained of an increased post-injection pain.…”
Section: Discussionmentioning
confidence: 99%
“…O que se sabe até o momento é que cada metodologia pode produzir um produto diferente, possivelmente com distintos potenciais terapêu-ticos (Ehrenfest et al 2009), e com variada quantidade e cinética de liberação dos fatores de crescimentos (Ehrenfest et al 2009, Mazzucco et al 2009, Sánchez et al 2009). Levando em consideração as definições básicas para esses componentes ricos em plaquetas, pode-se dizer que no presente estudo foi utilizado um PRP pobre em leucócitos (PRP-PL), o qual pode resultar, quando comparado com o PRP rico em leucócitos (PRP-RL), em menor resposta inflamatória aguda, menor celularidade e vascularização, conforme relatado por Dragoo et al (2012) cinco dias após tratamento de tendões de ratos com PRP-PL ou PRP-RL. De acordo com Wasterlain et al (2012), devido a dificuldade em separar os leucócitos das plaquetas durante a maioria dos protocolos adotados, não é raro se utilizar um PRP-RL, que não é adequado quando se deseja uma menor reação inflamatória.…”
Section: Discussionunclassified
“…Dragoo et al [21] showed that leukocyte-rich PRP had a greater inflammatory response relative to leukocyte-poor PRP at post-injection day 5, but there was no difference at day 14. McCarrel et al [22] demonstrated that leukocytereduced PRP had decreased levels of tumor necrosis factor alpha and interleukin 1 beta relative to standard PRP, highconcentration PRP, and concentrated-leukocyte PRP.…”
Section: Prp Duration Of Effectmentioning
confidence: 99%